PLANKTON COMMUNITY STRUCTURE ON FISH PONDS IN THE RIAM KANAN RIVER OF BANJAR REGENCY - Rieski Ambarwati; Krisdianto Krisdianto; Slamat Slamat (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2017)
Aquaculture in Riam Kanan river receives watersupply from rivers and Riam Kanan reservoir from upstream to downstream and practices different irrigation and fertilization systems. This study was aimed to compare the plankton community structure, to find out the physicalchemical parameters associated with the abundance of plankton and the fertility of the fish-farming ponds. The research was conducted at Mandiangin Freshwater Aquaculture Center (Balai Budidaya Air Tawar – BBAT), Karang Intan (Balai Benih dan Induk Ikan Air Tawar – BB-IAT) and Cindai Alus Minapolitan area by using the observation method. Water samples were taken by composite of 6 replicates at 12 stations. The parameters measured were temperature, visibility, pH, iron, free ammonia, nitrate, phosphate, DO, BOD and plankton analysis. Data were tested statistically with cluster, Pearson correlation and regression. The result shows that there are differences in plankton community structure in the fish ponds, shown by 5 cluster groups. The abundance of phytoplankton has a significant correlation with pH, temperature, DO, and free ammonia. The abundance of zooplankton also has a significant correlation with pH, DO, BOD, and free ammonia. The seed pond at BBAT Mandiangin is eutrophically dominated by Bacillarophyta and Amoboezoa, while in BB-IAT Karang Intan and Cindai Alus are dominated by Cyanophyta and Rotifera. The inlet channel of BB-IAT Karang Intan and the broodstock pond belong to mesotrophic category, predominance by Cyanophyta, Chlorophyta and Rotifer. BBIAT Karang Intan outlet ponds, BBAT Mandiangin inlet channel and Cindai Alus inlet pond are included in the oligotrophic category, predominance by Cyanophyta and Chlorophyta. Plankton community structure of the fishfarming pond varies even with the same ecological conditions.